Особенности плазмохимического травления торцов кремниевых пластин для фотоэлектрических преобразователей - Fedorovich, O. A.; Kruglenko, M. P.; Polozov, B. P. (PE "Politekhperiodika", Book and Journal Publishers, 2009)
Results of technological researches of plasmachemical reactor (PCR) for etching of silicon plate edges of photo-electric converters are described. Dependences of silicon etching speed on a discharge current, magnetic field intensity, quantity of the process able surface area and gases composition are resulted. Recommendations on technological use of PCR in an industrial production of photo-electric converters (PEC) are given. The productivity of PCR, developed in INR, is higher than productivity of the best foreign analogue of firm «Alkatel» more than in two times.